2005
DOI: 10.1007/s10495-005-0800-z
|View full text |Cite
|
Sign up to set email alerts
|

Cell death suppression by cytomegaloviruses

Abstract: Cytomegaloviruses (CMVs), a subset of betaherpesviruses, employ multiple strategies to suppress apoptosis in infected cells and thus to delay their death. Human cytomegalovirus (HCMV) encodes at least two proteins that directly interfere with the apoptotic signaling pathways, viral inhibitor of caspase-8-induced apoptosis vICA (pUL36), and mitochondria-localized inhibitor of apoptosis vMIA (pUL37 × 1). vICA associates with pro-caspase-8 and appears to block its recruitment to the death-inducing signaling compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 147 publications
0
57
0
Order By: Relevance
“…This could reflect the difference in Bak/Bax dependence between cell lines, as has been reported previously. 33 We found that Bak knockdown in uninfected and DF1L-infected cells protects equally well from apoptosis, as infection with WR virus protects the control knockdown cells (Figure 8d). We therefore favour that acute depletion of Bak lowers the total Bak/Bax burden on the cells.…”
Section: F1l Binds Bak To Inhibit Apoptosismentioning
confidence: 66%
“…This could reflect the difference in Bak/Bax dependence between cell lines, as has been reported previously. 33 We found that Bak knockdown in uninfected and DF1L-infected cells protects equally well from apoptosis, as infection with WR virus protects the control knockdown cells (Figure 8d). We therefore favour that acute depletion of Bak lowers the total Bak/Bax burden on the cells.…”
Section: F1l Binds Bak To Inhibit Apoptosismentioning
confidence: 66%
“…Inhibition can be achieved through indirect mechanisms such as the virus-induced downregulation of death receptor expression (116) or the expression of secreted viral TNF receptor homologs (9), both of which prevent signaling at the cell surface. An important general mechanism viruses use to suppress caspase activation is inhibition of mitochondrial membrane permeabilization, thus preventing or delaying the release of cytochrome c. These approaches utilized by viruses to prevent apoptosis have been reviewed in detail elsewhere (2, 14,17,39,47,61,107,113).…”
Section: Virus-mediated Inhibition Of Caspasesmentioning
confidence: 99%
“…vMIA contains two domains, a Nterminal mitochondrial localization sequence (MLS, aa 5-34) that does not undergo proteolytical removal (Mavinakere et al, 2006) and the Bax-binding domain (BBD, aa 115-147) (Arnoult et al, 2004;Poncet et al, 2004). These domains are together necessary and sufficient for vMIA-mediated cytoprotection, as determined by deletion mapping (Goldmacher et al, 1999(Goldmacher et al, , 2005, and are highly conserved among all tested clinical viral isolates (Hayajneh et al, 2001). The three-dimensional structure of vMIA has not been yet established by either NMR or crystal structure analysis.…”
Section: Introductionmentioning
confidence: 99%